A review of genetic advances on breeding salt tolerant crops - El Sharkawy H. (Reuse of low quality water for irrigation, 1989)
An efficient strategy for improving plants to be adapted to extreme environments would maximise the use of cultivated land and increase the utilisation of marginal soils. Because of the economic impact of stresses and the large amount of energy required to alter the environment to suit the plant, it is becoming increasingly important to utilise existing techniques to breed plants better adapted to stress. The purpose of this review is to summarise the advances and prospects for the genetic improvement of salt tolerance in cultivated crops. The genetic approach to the salinity problem is fairly new, but has generated considerable interest worldwide. This approach provides exciting prospects for increasing productivity in salt affected area.
Aswan Seminar, 1988/01/16-21, Cairo (Egypt)